2015
DOI: 10.3892/mmr.2015.3683
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor effect of resveratrol on chondrosarcoma cells via phosphoinositide 3-kinase/AKT and p38 mitogen-activated protein kinase pathways

Abstract: Abstract. Chondrosarcoma is one of the most common types of primary bone cancer that develops in cartilage cells. Resveratrol (Res), a natural polyphenol compound isolated from various fruits, has a suppressive effect on various human malignancies. It has been shown that Res inhibits matrix metalloproteinase (MMP)-induced differentiation in chondrosarcoma cells. However, the effects of Res on cell proliferation, apoptosis and invasion of chondrosarcoma cells, as well as the underlying mechanisms, remain largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…Lin et al (36) recenly proved that resveratrol was able to inhibit glucose-induced migration of vascular smooth muscle cells mediated by focal adhesion kinase via AKT and ERK signaling pathways. Dai et al (37) indicated that resveratrol suppressed chondrosarcoma cell invasion via AKT and p38 MAPK pathways. Here, we found that resveratrol was also able to inhibit hyperglycemia-induced invasion and migration abilities of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (36) recenly proved that resveratrol was able to inhibit glucose-induced migration of vascular smooth muscle cells mediated by focal adhesion kinase via AKT and ERK signaling pathways. Dai et al (37) indicated that resveratrol suppressed chondrosarcoma cell invasion via AKT and p38 MAPK pathways. Here, we found that resveratrol was also able to inhibit hyperglycemia-induced invasion and migration abilities of pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, resveratrol could down‐regulate miR‐21, which is up‐regulated in ALD and related to cell apoptosis (Francis et al., ), remodeling, and liver regeneration (Dippold et al., ) in human SW480 colon cancer cells. Therapeutic effect of resveratrol on other diseases through epigenetic regulation has also been reported (Dai et al., ; Zhang et al., ). Therefore, resveratrol could possibly reverse or cure ALD through epigenetic regulation, which needs further investigation.…”
Section: Reversing Epigenetic Alterations For Ald Therapymentioning
confidence: 91%
“…By western blot analysis, it was demonstrated that the PI3K, Akt and AMPK levels decreased significantly in a concentration of resveratrol enough to cause apoptosis. This result suggest that the inhibition of PI3K pathway by resveratrol may be a molecular mechanism to suppress cancer cell proliferation [335]. …”
Section: Cellular Deathmentioning
confidence: 99%